Influência da composição monomérica e da presença de sal difenil-iodônio nas propriedades mecânicas de resinas experimentais reforçadas com fibras de vidro - Carvalho, Pedro Ivo de (2017)
Several researches aim to discover a best development of new glass-fiber-reinforced composite resins for the manufacture of intraradicular posts with better mechanical properties has been the aim of several researches lately. The reinforcement of composite resin with glass fibers can improve the mechanical properties, such as flexural strength, fracture resistance and compressive strength. Considering that the resin matrix monomers, the photoinitiator system and the interaction with the glass fibers interfere in the homogenization of the composite and in the degree of polymer conversion, the present work had as Objective: To evaluate the influence of different proportions of the monomers Bis-EMA / Bis-GMA / TEGDMA and photoactivator systems based on DFI and camphorquinone on the mechanical properties of a experimental fiberglass reinforced composite resin. Methodology: Ten groups were created (n = 10) using an experimental resin based on methacrylate, having as study factors: 1. Different matrices according to the proportions of monomers Bis-GMA (BG), TEGDMA (TE) and Bis-EMA (BE): And 2. The photoinitiator system: without DFI (SD) salt or DFI (CD) salt. The samples were prepared for the flexural strength (RF) and diametral tensile strength (RTD) tests. Statistical analysis showed that for RF (Mpa) there was significance in the interaction between the factors under study (p = 0.047). The highest result occurred for Group 10 (267.815 ± 45.05) c, followed by Group 9 (242.440 ± 44.83) bc; Group 8 (241.05 ± 44.83) b Group 3 (236.152 ± 26.42) abc. The lowest result occurred in Group 9 (192.450 ± 12.60) a, followed by Group 7 (202.35 ± 28.36) ab; Group 6 (207,240 ± 30,07) ab; Group 2 (209.530 ± 23.16) ab; Group 5 (216,760 ± 30,14); And Gruop 1 (218,880 ± 41,49). For RTD only the presence of DFI salt showed statistical significance (p = 0.001). The addition of the DFI salt in the composite significantly increased results for flexural strength and diametral tensile strength, while the increase of Bis-EMA was significant for better flexural strength results.